Reorienting Community Institutions: for Cohesive Management of Natural Resources - Pathan, R. S. (Indian Forester, 2011)
Establishing organic unity through structural changes and devolution of authority in favour of communities, as envisaged under various schemes of Rural Development or National Afforestation Programme in India, appear to be challenging task as the activities are solely physical and confined to a brief period of a year or two. The community institutions, otherwise under severe external influences, may need reorientation through matching social inputs and inspiring follow-ups else the organic unity that anchored in institutional strength may remain at large. Reorienting the social institution, for the purpose, is a long drawn process and may have to traverse through the identification of the status of existing coherency and factors contributing the same, the activities those preferred for cooperation, inputs necessary to establish favourable conditions for preferred activities, augmenting those factors, experiencing the activities, confidence building, trying the activity of second preference, confidence building, repeat and extending the cooperation to long term activity of conservation. The paper attempts to suggest a fresh approach to explore the rural intricacies related to social relationships, to generate the valuable knowledge in shaping the methods of inquiry and application in rural situations and to help in sustaining the involvement of communities in participatory natural resource management.